A comparison of marginal bone loss, survival rate, and prosthetic complications in implant-supported splinted and nonsplinted restorations: A systematic review and meta-analysis - Aesha Harsh Shah; Pankaj Patel; Aumkar Trivedi; Adit Shah; Nikki Desai; Mitangi Talati (Wolters Kluwer Medknow Publications, 2022)
Aim: To compare marginal bone loss (MBL), implant survival rate and prosthetic complications of implant-supported splinted and non-splinted restorations (NSR). Settings and Design: This systematic review was conducted in accordance with the Preferred Reporting Items for Systematic reviews and Meta-Analyses guidelines (PRISMA). The PROSPERO registry, which keeps track of prospective systematic reviews, also received this paper (CRD42021229477). Material and Methods: An electronic search was done in PubMed, the Cochrane Central Trials Register, Scopus, Science Direct, and Google Scholar searches were carried out. The search was limited to articles published in English and covered the period from January 2010 to August 2020. Statistical Analysis Used: To conduct the meta analysis, researchers employed methodologies such as continuous measurement and odds ratios. Results: For both qualitative and quantitative analysis, 19 scientific studies were chosen. 3682 implants were placed in 2099 patients with a mean age of 59 years (splinted, 2529; non-splinted, 1153); the mean age was not provided in 5 trials. For splinted restorations, there were statistically significant differences in MBL, indicating the former has less MBL than for NSR. Splinted restorations had much greater survival rates than NSR, according to a qualitative study. Rest prosthesis complications with or without splinting were essentially the same. Conclusions: Splinted implant restorations lost less bone than non-splinted implant restorations, according to this meta analysis. This was particularly true for posterior restorations. Lower implant failure was associated with splinted restorations. Restorations with and without splinting had the same level of prosthetic problems.